Assessing the ability of public spaces in cities to face future pandemics: the case of Sheikh Daher Square in Lattakia city - دلالة ليليان أحمد; جورج قنصلية; طارق بركات (Tishreen University Journal -Engineering Sciences Series,, 2023)
The spread of diseases has become a reality that the world suffers from. Despite this, the strategy to prevent its effects is not effective at all environmental, social and cultural levels. The restrictions imposed by the Corona pandemic on the use of public spaces and physical distancing were among the most important measures taken to reduce the transmission of the Corona pandemic and protect public health. As much attention has been paid to medical experts and following government guidelines, while urban planning and design play a major role in confronting the pandemic if not ignored, it has become important to know the long-term effects of the Corona epidemic on public spaces after lifting restrictions. The research deals with public spaces in the city of Lattakia in the face of pandemics, as it sheds light on some of the principles and foundations adopted globally in this field, through which a number of criteria are identified that can contribute to evaluating the ability of urban spaces within the city to face future pandemics. Then an analytical study is conducted for one of the main public spaces in the city of Lattakia (Sheikh Dhaher Square) based on these criteria, with the aim of determining the extent to which the space is achieved for each of them, and thus identifying its strengths and weaknesses in this area. The research concludes with a set of results that determine the reality of public spaces in the city of Lattakia. Based on that, it proposes some recommendations that can contribute to addressing weaknesses and strengthening points of strength in the field of the ability of public spaces in the city of Lattakia to face future pandemics.